2023
DOI: 10.5114/aoms/170159
|View full text |Cite
|
Sign up to set email alerts
|

The effect of trehalose administration on the serum expression levels of microRNAs associated with lipid metabolism and autophagy process in patients with myocardial infarction - the post-hoc analysis of the TREAT-IR trial.

Abstract: IntroductionThis study aimed to evaluate the TRE-induced changes in the serum expression levels of miRNAs associated with lipids metabolism and autophagy process in MI patients to assess the potential protective effects of TRE in these patients.Material and methodsThis post hoc investigation was performed on serum samples obtained from a pilot randomized, double blind, placebo-controlled clinical trial that recruited 14 men (aged 18-80) who had MI and systemic inflammation. The patients were randomized in a 2:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Likewise, the administration of trehalose to rats with spinal cord injury decreased the IL- 1β, TNF-α, and nitric oxide levels [ 42 ]. It is suggested and confirmed by several animal studies that trehalose administration is effective in treatment of various conditions such as neurodegenerative disorders [ 43 , 44 ] including Parkinson's [ 45 , 46 ], Alzheimer's [ [47] , [48] , [49] ], and Huntington's diseases, atherosclerosis [ 50 , 51 ], stroke [ 52 ], fatty liver disease [ 53 , 54 ], diabetes mellitus type II [ [55] , [56] , [57] , [58] ], and pulmonary edema [ 37 ]. Although trehalose is composed of two glucose molecules, several clinical trials have shown its effect on lowering insulin resistance and preventing metabolic syndrome and type 2 diabetes [ [59] , [60] , [61] ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the administration of trehalose to rats with spinal cord injury decreased the IL- 1β, TNF-α, and nitric oxide levels [ 42 ]. It is suggested and confirmed by several animal studies that trehalose administration is effective in treatment of various conditions such as neurodegenerative disorders [ 43 , 44 ] including Parkinson's [ 45 , 46 ], Alzheimer's [ [47] , [48] , [49] ], and Huntington's diseases, atherosclerosis [ 50 , 51 ], stroke [ 52 ], fatty liver disease [ 53 , 54 ], diabetes mellitus type II [ [55] , [56] , [57] , [58] ], and pulmonary edema [ 37 ]. Although trehalose is composed of two glucose molecules, several clinical trials have shown its effect on lowering insulin resistance and preventing metabolic syndrome and type 2 diabetes [ [59] , [60] , [61] ].…”
Section: Introductionmentioning
confidence: 99%